Micro-distribution of freshwater snails before and after water flow events in hydraulic structures in Tessaout Amont Irrigation System, Morocco - Laamrani, Hammou; Madsen, H.; Boelee, Eline (Informa UK Limited, 2009)
Bulinus truncatus, the intermediate host of Schistosoma haematobium, is widely distributed in modern irrigation schemes in Morocco. These schemes have intermittent irrigation and canals dry out in between irrigation periods. The snail species is therefore associated with the 'siphon boxes' connecting canal segments, as these contain water that stagnates between irrigation cycles. The micro-distribution of snails in siphon boxes, was studied before and after one irrigation period, to identify factors that could be manipulated in order to control this snail species. Density of B. truncatus, Ancylus fluviatilis, Lymnaea peregra and Melanopsis praemorsa varied significantly with water depth before and after irrigation. The pulmonate snail species had the highest densities at depths ranging between 20 and 80 cm. After an irrigation period of 10 to 12 hours B. truncatus, A. fluviatilis and L. peregra were relatively more abundant at the bottom of the siphon boxes than in the upper sections. Aggregation at the corners of the boxes could be among the factors that enable snail species to avoid the detrimental effect of turbulent water flow during irrigation. The relevance of changes in density and micro-distribution following an irrigation cycle in the control of B. truncatus is discussed.